Screening and validation of 3’-Methoxydaidzein as a therapeutic agent in ulcerative colitis based on disulfidptosis-associated molecular clusters - Jie Yuan; Chongyong Gao; Wang Xin; Fanlin Meng; Hong Zhang (PLoS ONE, 2025)
Background Ulcerative colitis (UC) is a recurrent inflammatory condition of the bowel with a multifaceted pathogenesis, including programmed cell death, oxidative stress, and immune-mediated inflammation. As a recently identified type of cell death, disulfidptosis has an unclear role in UC. Methods We analyzed clusters of disulfidptosis-related genes (DRGs) and immune cell infiltration in 361 patients with UC from the GSE73661and GSE92415 datasets. Differentially expressed genes (DEGs) were identified using unsupervised clustering methods, and hub genes were selected using machine learning algorithms. Additionally, potential key components of potential traditional Chinese medicines for the treatment of UC were predicted based on hub genes. Finally, experimental validation was performed through qRT-PCR, western blotting, and immunohistochemistry. Results We identified two molecular clusters related to disulfidptosis, each showing significant heterogeneity in gene expression and immune profiles. Hub genes associated with disulfidptosis, CXCL1, HMGCS2, AQP8, and SLC26A2, were further screened and validated. Additionally, potential traditional Chinese medicines for UC were predicted. 3’-Methoxydaidzein (MHD), a key constituent of Puerariae Radix, inhibited LPS-induced inflammatory responses in Caco2 cells and alleviated DSS-induced colonic injury in UC mice via upregulation of SLC26A2. Conclusion DRGs demonstrate strong discriminatory power in distinguishing UC subtypes. Cluster with high expression of SLC26A2 showed a UC phenotype with a milder degree of damage. Additionally, we identified the hub gene SLC26A2 as playing a significant role in UC, and MHD demonstrates potential as a targeted therapeutic strategy for UC.